The Ashâarite Dogma: the Root of the Arab/Muslim Absolutism - Mabrook, Ali (Al-Jamiah: Journal of Islamic Studies, 2008)
There are three major categories upon which all of the worldâs civilizations are established, namely, God, Man and World. The differentiation of worldly civilizations and the diversity of systems of knowledge are due to the way of drawing up the relation thereby the three categories are arranged. Some scholars assumed that these categories are communicated and totally correlated each other, in a way that each cannot be realized except in its connectivity to the others. While some others thought that the three categories should be separated and disconnected, in a way that each of the three is realized as an absolute and dominant one while the two others are marginal and dependent ones. Needless to say, while the first perception provokes the values of tolerance and the acceptance of the other, the second one motivates absolutism and the negation of the other. Unfortunately the Ashâarism, not only a dogma but âand more importantlyâ a stable and dominant way of thinking, is stimulated by the second perception based on an absolutism and the negation of the other. It departs from that historical fact that this paper argues that absolutism, manifested in political, religious and cultural aspects of nowadays Muslims life, can be related to the dominance ofAshâarism all over the Muslim world.